“Jeyn Eyr” asarining o’zbek tiliga tarjima qilish jarayonidagi muammolar (Journal of Universal Science Research, 2025)
This article discusses the lexical, grammatical, and stylistic problems encountered in the translation of the English writer Charlotte Bronte's "Jane Eyre" into the Uzbek language. The novel "Jane Eyre" is considered one of the most important works in English literature, in which the ideas of feminism and humanism are put forward. The translation into the Uzbek language was carried out through the Russian language.